Applications of Shell-like Curves Connected with Fibonacci Numbers - Ala Amourah; Ibtisam Aldawish; Basem Aref Frasin; Tariq Al-Hawary (Axioms, 2023)
We introduce a new subclass <semantics>JΣη,δ,μ(<mover accent="true">p˜</mover>)</semantics> of bi-univalent functions, defined by shell-like curves connected with Fibonacci numbers. Our main results in this paper include estimates of the Taylor–Maclaurin coefficients <semantics><mfenced separators="" open="|" close="|">a2</mfenced></semantics> and <semantics><mfenced separators="" open="|" close="|">a3</mfenced></semantics> for functions in this subclass, as well as solutions to Fekete–Szegö functional problems. We also show novel outcomes resulting from the specialization of the parameters used in our main results.